Architecture as a Bridge Between The Rich and The Poor? In a World Struggling with Climate Crises, Population Growth and Globalisation – The Example of Bali - Ellmann, Laura (Journal of A Sustainable Global South, 2024)
This academic paper explores the potential of architecture to act as a bridge between social inequalities, particularly in the context of a world struggling with climate crises, population growth and globalisation. Using the specific case of Bali, the study examines the global trends of population growth, climate crisis, the widening gap between rich and poor and the crucial role of architecture in shaping living conditions. Through an analysis of slums, their architectural characteristics and the contrasting affluent globalised architecture, the project aims to explore whether architecture can act as a catalyst for social inclusion. In addition, the concept of “home“ will be analysed to provide insights into the emotional and functional dimensions of living spaces. Finally, based on a comprehensive evaluation of relevant literature and examples, a forward-looking perspective on the changes needed in architecture to overcome social inequalities will be presented. Index Terms — architecture, gap, home, poor, rich, slum